The Development of Concept Attainment Model (CAM)-Based Student Worksheets (LKPD) on Cell Concepts for Eleventh Grade Students at SMA Negeri 10 Gowa - Nur Ifna; Ainul Uyuni Taufiq; Andi Tenri Ola Rivai; St. Syamsudduha; Hamansah (UNIVERSITAS KHAIRUN, 2026)
This study is motivated by the low understanding of the concept of students on the subject of cells, especially transport across membranes, due to the abstract nature of the subject and the lack of materials that encourage independent concept discovery. The purpose of this study is to develop a Student Work Sheet based on the Concept Attainment Model and to test its validity, practicality, and effectiveness in biology classes for 11th grade students at SMAN 10 Gowa. The research and development method used is ADDIE, which includes analysis, design, development, implementation, and evaluation. The study involved 31 students in the 11th grade. The instruments included a validation sheet, a survey of teachers and students, and a learning outcome test. The results of the study showed that the LKPD based on CAM was highly valid, practical, and effective. Penggunaan LKPD membantu siswa mengidentifikasi ciri-ciri konsep melalui contoh dan noncontoh, meningkatkan keterlibatan aktif, dan memperkuat pemahaman konseptual. Therefore, the LKPD based on the Concept Attainment Model is suitable for use as an alternative teaching material for biology lessons on cells in secondary schools.